EARLY CHECKING OF GENETIC STABILITY OF CORK OAK SOMATIC EMBRYOS BY AFLP ANALYSIS. - Hornero, J; Martinez, I; CELESTINO, C; Gallego, F J; Torres, V; TORIBIO, M (International Journal of Plant Sciences, 2001)
Early checking of the genetic stability, of tissue culture-derived plants is necessary to obtain all the potential benefits of clonal forestry. Previous work in Quercus suber L. using random amplified polymorphic DNA (RAPD) markers showed no genetic variation among somatic embryos within embryogenic lines of zygotic origin. Genetic fingerprinting based on amplified fragment length polymorphisms (AFLP) allows the direct analysis of variation at the entire DNA level by generating more reproducible markers than RAPDs. To confirm the absence of genetic variation within six embryogenic lines of zygotic origin, six primer pairs were selected out of 48 combinations of primers for revealing up to 512 AFLP markers, 301 of them (58.8%) being polymorphic. The mean number of markers per genotype was 375. Again differences were recorded among embryogenic lines, even between those that arose from half-sib zygotic embryos, but no variation was observed among somatic embryos within embryogenic lines. To check variation in embryogenic lines raised from non-embryonic tissues, somatic embryogenesis was induced in expanding leaves collected from sprouts originating in three mature cork oak. DNA was extracted from leaves and from somatic embryos derived from each tree, and three primer pairs showed 165, 110, and 108 markers per genotype/tree, respectively. In one tree, AFLP patterns generated from leaves and somatic embryos were identical, but variation was detected in samples from the other two trees. Although the level of genetic variation detected in these lines (5.6% and 7.3% of polymorphism, respectively) is lower than that recorded for half sibs of cork oak (25%–31%), its influence on phenotypic variation needs further assessment. [ABSTRACT FROM AUTHOR]
Keywords: AFLP; Cork oak; DNA markers; in vitro culture; Quercus suber; somaclonal variation; Somatic embryogenesis

Testing the conservation of Quercus spp. microsatellites in the cork oak, Q-suber L. - Hornero, J; Gallego, F J; Martinez, I; TORIBIO, M (SILVAE GENETICA, 2001)
The transferability of microsatellite (SSR) loci from Quercus spp. to cork oak (Quercus suber L.) was investigated. Semi-automated analysis of fluorescently-labelled PCR fragments was used to test 24 primer sets developed for Q. myrsinifolia BLUME, Q. petraea (MAT7.) LIEB. and Q. robur L. in 41 cork oak trees from four stands covering the main area of distribution of the species in Spain. Successful cross-species events occurred for 13 loci (54%). Two of them were monomorphic and another two appeared as multilocus. High levels of genetic variability were detected both for the number of alleles, 62 (7.5 per polymorphic locus, with a maximum number of 19 in locus ssrQpZAG110) and for the expected heterozygosity (mean H-E = 0.648). These results were much higher than those previously reported by other authors using allozyme loci. The usefulness of the. SSR loci successfully amplified for studies on population genetics of cork oak is discussed.
Keywords: Cork oak; Fagaceae; microsatellites; Quercus suber

Etiology of oak decline in Spain - Gallego, F J; de Algaba, A Perez; Fernandez-Escobar, R (European Journal of Forest Pathology, 1999)
In different areas of Extremadura, Western Spain, soil samples were taken at the bottom of holm oak (Quercus ilex) trees that were showing decline symptoms. Half of each sample was sterilized, and acorns were sown in both sterilized and nonsterilized soil samples. The resulting seedlings were used as baits for the isolation of fungi. Seedlings growing on the natural, nonsterilized substrate were characterized by having a lower vegetative growth than the ones growing on the sterilized soil samples, and most of them died. Phytophthora dnnamomi was consistently isolated from their roots. Fusarium oxysporum was also isolated as well as different species of Pythium, although to a lesser extent. Pathogenicity tests were performed on holm oak seedlings with five different isolates of P. chinnamomi, with F. oxysporum, Pythium and with a mixture of the three fungi. All the inoculated seedlings with P. chinnamomi developed root rot and grew slowly, and 35.7% of them died up to the end of the experiments. P. chinnamomi was consistently isolated from their roots, indicating that this fungus is the causal agent of holm oak decline. However, F. oxysporum caused similar symptoms on oak seedlings as P. chinnamomi, and was isolated also from the roots, although its frequency was lower than that of. P. cinnamomi.
Keywords: Holm oak; Oak decline; Pathogenicity; Phytophthora cinnamomi (PG)

Treatment of oak decline using pressurized injection capsules of antifungal materials - Fernandez-Escobar, R; Gallego, F J; Benlloch, M; Membrillo, J; Infante, J; de Algaba, A Perez (European Journal of Forest Pathology, 1999)
Quercus ilex and Quercus suber trees growing at several sites in Extremadura, Western Spain, that were showing symptoms of oak decline were injected with potassium phosphonate, quinosol or carbendazim using a low-pressure method of trunk injection composed of a pressurized capsule system. A team of four people injected between 120 and 189 trees per day, depending upon the density of the undergrowth vegetation. This labour cost represented, approximately, 15–20% of the total cost of the treatment. The potassium phosphonate-injected trees showed a significant improvement in vegetative growth within 2 years of the injection treatment, and they also showed some recovery from the decline symptoms during the third year. Only one injection treatment of an average of 3.5 capsules (corresponding to 24.5 g phosphonic acid) per tree of approximately 36 cm in diameter, was necessary to reduce the disease severity significantly. Indirectly, these results corroborate the implication of Phytophthora cinnamomi in oak decline within Spanish Quercus woodlands.
Keywords: Oak decline; phosphonic acid; trunk injections (PG)

Testing somaclonal variation using RAPDs in Quercus suber L. somatic embryos. - Gallego, F J; Martinez, I (International Journal of Plant Sciences, 1997)
Focuses on the use of Random Amplified Polymorphic Deoxyribose nucleic acid (RAPD) profiles to test somaclonal variation in Quercus suber L. somatic embryous during recurrent embryogenesis. Number of primers used to amplify DNA from isolated embryos; Use of somatic embryogenesis from immature zygotic embryos; How somaclonal variation was detected.
Keywords: Cork oak; SOMATIC embryogenesis (citation)